The Use of Convolutional Neural Networks in Multiclass Classification of Digital Pictures - Marta BISTROŃ; Zbigniew PIOTROWSKI (Communications of International Proceedings, 2021)
The article shows a problem of digital picture classification with the use of convolutional neural networks in a multiclass classification problem. It describes basic problems related to the classification of data sets with a very large number of classes, and basic picture preprocessing operations. It presents the convolutional neural network model in use, its training procedure and the results of the experiment on a set containing a large number of classes – Stanford Dogs.
Keywords: CNN; Digital Image Classification; Multi-Class Classification; Image Preprocessing.